Application Analysis of Information Technology in the Yellow River Flood Control Project Management. Issue 1 (May 2021) - Zhanjun, Yuan; Liang, Zhao
Abstract: The central task of the Yellow River flood control works management is to maintain the integrity of the project and ensure the flood control ability of the project does not decrease. In order to achieve this goal, the Yellow River management departments at all levels need to use modern technology to supervise a set of modern project management system, so as to understand and grasp the project operation status in real time, so as to timely find and eliminate the project hidden dangers, and ensure the safety of the downstream embankment and flood control operation.